Large area chemical vapor deposition growth of monolayer MoSe2 and its controlled sulfurization to MoS2. Issue 7 (28th January 2016) - Ghosh, Rudresh; Kim, Joon-Seok; Roy, Anupam; Chou, Harry; Vu, Mary; Banerjee, Sanjay K.; Akinwande, Deji
Abstract: Abstract : Layered transition metal dichalcogenides which are part of the two dimensional materials family are experiencing rapidly growing interest owing to their diverse physical and optoelectronic properties. Large area controllable synthesis of these materials is required for transition from lab scale research to practical applications. In this work, we present a single step chemical vapor deposition process for large area monolayer growth of molybdenum selenide (MoSe2 ). We also demonstrate controllable thermal conversion from molybdenum selenide to molybdenum sulfide.